SARS-CoV-2 vaccine based on ferritin complexes with screened immunogenic sequences from the Fv-antibody library - Jung, Jaeyong; Kim, Tae-Hun; Park, Jae-Yeon; Kwon, Soonil; Sung, Jeong Soo; Kang, Min-Jung; Jose, Joachim; Lee, Misu; Shin, Hyun-Jin; Pyun, Jae-Chul (Royal Society of Chemistry, 2025)
In this study, the vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was developed using ferritin complexes with the immunogenic sequences screened against the SARS-CoV-2 spike protein (SP) from the Fv-antibody library. The Fv-antibody library was prepared on the outer membrane of E. coli by the expression of the VH region of immunoglobulin G (IgG) with a randomized complementarity-determining region 3 (CDR3). Four Fv-antibodies to the receptor-binding domain (RBD) were screened from the Fv-antibody library, which had a comparable binding constant (KD) between SARS-CoV-2 SP and the angiotensin-converting enzyme 2 (ACE2) receptor. The binding sites of screened Fv-antibodies on the RBD were analyzed using a docking analysis, and these binding sites were used as immunogenic sequences for the vaccine. The four immunogenic sequences were modified and co-expressed as a part of ferritin which was assembled into a ferritin complex. After the vaccination of ferritin complexes to mice, the anti-sera were analyzed to have a high enough titer. Additionally, the immune responses were found to be activated by vaccination, such as the expression of IgG subclasses and the increased level of cytokines. The neutralizing activity of the anti-sera was estimated using a cell-based infection assay based on pseudo-virus expressing the SP of SARS-CoV-2 variants.